Finite Element Modeling and Analysis of Drive Chain - Nanade, Sunny H. (My University, 2012)
The process of Drive Chain Analysis is as important as its production. In today’s era, it’s an intelligent and profit making job to produce an optimum product. Currently, testing of chains requires machines on which a specimen is mounted and testing is done. These testing are carried out at hourly, daily or monthly rates depending upon the type of test. Some test machines are limited to a particular dimension of the product. Many changes have to be done in production as well as testing machines if it is thought to change the dimension of product, which needs a huge amount of money, time and manpower. Even if the work is limited to the testing of finished parts, there are many tests which cannot favour dimensional change. Use of computer software’s can help us a lot in the field of optimization. Models for Ultimate Testing, Endurance Testing, and Fatigue Analysis can now days be successfully analysed on a computer. Models whose output agrees with the data form the existing test machines were tried to be made, once done, the chain was optimized based on the constraints.
M.E. (CAD/CAM and Robotics)
Keywords: Drive chain; tensile test; fatigue Test; endurance Test; finite element